A novel host-adapted strain of Salmonella Typhimurium causes renal disease in olive ridley turtles (Lepidochelys olivacea) in the Pacific - Thierry, Work (2019)
Salmonella spp. are frequently shed by wildlife including turtles, but S. enterica subsp. enterica serovar Typhimurium or lesions associated with Salmonella are rare in turtles. Between 1996 and 2016, we necropsied 127 apparently healthy pelagic olive ridley turtles (Lepidochelys olivacea) that died from drowning bycatch in fisheries and 44 live or freshly dead stranded turtles from the west coast of North and Central America and Hawaii. Seven percent (9/127) of pelagic and 47% (21/44) of stranded turtles had renal granulomas associated with S. Typhimurium. Stranded animals were 12 times more likely than pelagic animals to have Salmonella-induced nephritis suggesting that Salmonella may have been a contributing cause of stranding. S. Typhimurium was the only Salmonella serovar detected in L. olivacea, and phylogenetic analysis from whole genome sequencing showed that the isolates from L. olivacea formed a single clade distinct from other S. typhimurium. Molecular clock analysis revealed that this novel clade may have originated as recently as a few decades ago. The phylogenetic lineage leading to this group is enriched for non-synonymous changes within the genomic area of Salmonella pathogenicity island 1 suggesting that these genes are important for host adaptation.